VALIDITY OF COMPUTER-BASED ELECTROLYTE FISHER GAME TO DEVELOP PROBLEM-SOLVING SKILL OF STUDENTS IN ELECTROLYTE AND NONELECTROLYTE SOLUTION (Universitas Negeri Surabaya, 2020)
The aim of this research was to get a valid computer-based Electrolyte Fisher game to develop problemsolving skill of students on electrolyte and nonelectrolyte solution topics so it could be used in learningactivity. The type of this research was development research by using 4D model with four stages includingdefine, design, develop, and disseminate, but the stages carried out in this research only until developmentstage. Validity was determined by two chemistry lecturers and one chemistry teacher. Research resultsproved that Electrolyte Fisher game was valid based on content validity percentage of 84.44% and constructvalidity percentage of 85.37%. There were three criteria assessed in content validity including thecorrectness of concepts in matter obtaining a percentage of 86.67%; the suitability of matter with learningobjectives obtaining 86.67%; and the suitability of game with problem-solving skill component obtaining80.00%. There were two criteria assessed in construct validity, namely the suitability of game with learningmedia requirements which included nine aspects obtaining percentage of 87.78% and the suitability ofdisplay quality in game which included three aspects obtaining 82.96%. Based on results of this researchshowed that the computer-based Electrolyte Fisher game to develop students’ problem-solving skill wasdeclared valid.Key words: electrolyte fisher game, problem-solving skill, electrolyte, and nonelectrolyte solution.